Serum milk fat globule-EGF factor 8 protein as a potential biomarker for metabolic syndrome - Lee, Han Ah (Clin Mol Hepatol, 2021)
BACKGROUND/AIMS: Useful biomarkers for metabolic syndrome have been insufficient. We investigated the performance of serum milk fat globule-EGF factor-8 (MFG-E8), the key mediator of inflammatory pathway, in diagnosis of metabolic syndrome. METHODS: Subjects aged between 30 and 64 years were prospectively enrolled in the Seoul Metabolic Syndrome cohort. Serum MFG-E8 levels were measured at baseline. RESULTS: A total of 556 subjects were included, comprising 279 women (50.2%) and 277 men (49.8%). Metabolic syndrome was diagnosed in 236 subjects (42.4%), and the mean MFG-E8 level of subjects with metabolic syndrome was significantly higher than that of subjects without metabolic syndrome (P<0.001). MFG-E8 level was significantly correlated with all metabolic syndrome components and pulse wave velocity (all P<0.05). Subjects were categorized into two groups according to the best MFG-E8 cut-off value as follows: group 1, MFG-E8 level <4,745.1 pg/mL (n=401, 72.1%); and group 2, MFG-E8 level ≥4,745.1 (n=155, 27.9%). At baseline, metabolic syndrome in group 2 was significantly more prevalent than in group 1 (63.9% vs. 34.2%, P<0.001). During median follow-up of 17 months, metabolic syndrome developed in 122 (38.1%) subjects among 320 subjects without it at baseline. The incidence of metabolic syndrome in group 2 was significantly higher than that in group 1 (55.4% vs. 34.5%, P=0.003). On multivariate analysis, MFG-E8 level ≥4,745.1 pg/mL was an independent predictor for diagnosis and development of metabolic syndrome after adjusting other factors (all P<0.05). CONCLUSIONS: Serum MFG-E8 level is a potent biomarker for the screening and prediction of metabolic syndrome.